Mannose receptor‐derived peptides neutralize pore‐forming toxins and reduce inflammation and development of pneumococcal disease - Karthik Subramanian; Federico Iovino; Vasiliki Tsikourkitoudi; Padryk Merkl; Sultan Ahmed; Samuel B Berry; Marie‐Stephanie Aschtgen; Mattias Svensson; Peter Bergman; Georgios A Sotiriou; Birgitta Henriques‐Normark (EMBO Molecular Medicine)
Abstract Cholesterol‐dependent cytolysins (CDCs) are essential virulence factors for many human pathogens like Streptococcus pneumoniae (pneumolysin, PLY), Streptococcus pyogenes (streptolysin O, SLO), and Listeria monocytogenes (Listeriolysin, LLO) and induce cytolysis and inflammation. Recently, we identified that pneumococcal PLY interacts with the mannose receptor (MRC‐1) on specific immune cells thereby evoking an anti‐inflammatory response at sublytic doses. Here, we identified the interaction sites between MRC‐1 and CDCs using computational docking. We designed peptides from the CTLD4 domain of MRC‐1 that binds to PLY, SLO, and LLO, respectively. In vitro, the peptides blocked CDC‐induced cytolysis and inflammatory cytokine production by human macrophages. Also, they reduced PLY‐induced damage of the epithelial barrier integrity as well as blocked bacterial invasion into the epithelium in a 3D lung tissue model. Pre‐treatment of human DCs with peptides blocked bacterial uptake via MRC‐1 and reduced intracellular bacterial survival by targeting bacteria to autophagosomes. In order to use the peptides for treatment in vivo, we developed calcium phosphate nanoparticles (CaP NPs) as peptide nanocarriers for intranasal delivery of peptides and enhanced bioactivity. Co‐administration of peptide‐loaded CaP NPs during infection improved survival and bacterial clearance in both zebrafish and mice models of pneumococcal infection. We suggest that MRC‐1 peptides can be employed as adjunctive therapeutics with antibiotics to treat bacterial infections by countering the action of CDCs.